TRANSFORMASI PENDIDIKAN ISLAM PESANTREN BAGI MUSLIM KELAS MENENGAH - Nashrullah Nashrullah; Hasan Ruzakki; Husniyatus Salamah Zainiyati; Suryani Suryani (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2023)
Actualization of modernism of Islamic educational institutions in the Pesantren environment is a necessity that should be considered. Some pesantren try to maintain aspects and values that characterize the pesantren itself, but others prioritize one aspect and actually eliminate other aspects, such as a simple lifestyle. This research uses a literature review system to collect related articles systematically. The results showed that the principle of orientation of Islamic education in pesantren today is still the same as before but is more likely to be more consumptive in adjusting to market needs which are considered as the future path of children. Pesantren that was once synonymous with a simple lifestyle, is now far from simple or more luxurious with superior facilities than before. The development of management and the changing pesantren system showed something different and provided a separate segment for the Muslim middle class as an option where their children deepened their religious education.